Investment Size and Firm's Value under Profit Sharing Regulation - Michele Moretto; Paolo Panteghini; Carlo Scarpa (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this article we analyse the effects of different regulatory schemes (price cap and profit sharing) on a firm's investment of endogenous size. Using a real option approach in continuous time, we show that profit sharing does not affect a firm's start-up decision relative to a pure price cap scheme. Unless the threshold after which profit sharing intervenes is very high, however, introducing a profit sharing element delays further investments: this decreases the present value of total investment. We also evaluate the reduction in the firm's value due to profit sharing, linking this reduction to the option value of future investments.
Keywords: D81; D92; G31; L51; 330; regulation; investment; profit sharing; real options; RPI-x